1978
DOI: 10.1051/rnd:19780312
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationships between the oocyte and somatic cells within the Graafian follicle of mammals

Abstract: Introduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
2

Year Published

1981
1981
1991
1991

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 15 publications
0
5
2
Order By: Relevance
“…The fact that higher levels of PRL were found in FF of intermediate OCCC than mature OCCC may reflect a higher vascular permeability to PRL in follicles yielding an intermediate OCCC, or alternatively, a process that increases levels in these follicles against the serum concentration. It has been suggested that PRL may stimulate the formation of an oocyte maturation inhibitor and that treatment of cultured rat follicles with an anti-PRL serum induced meiotic maturation (22). Our results strongly negate this possible effect of PRL on human oocytes, since high FF PRL concentrations were associated with successful fertilization and pregnancy, and may indicate that PRL might have a beneficial stimulatory role in the maturation process of the human oocyte.…”
Section: Discussioncontrasting
confidence: 68%
“…The fact that higher levels of PRL were found in FF of intermediate OCCC than mature OCCC may reflect a higher vascular permeability to PRL in follicles yielding an intermediate OCCC, or alternatively, a process that increases levels in these follicles against the serum concentration. It has been suggested that PRL may stimulate the formation of an oocyte maturation inhibitor and that treatment of cultured rat follicles with an anti-PRL serum induced meiotic maturation (22). Our results strongly negate this possible effect of PRL on human oocytes, since high FF PRL concentrations were associated with successful fertilization and pregnancy, and may indicate that PRL might have a beneficial stimulatory role in the maturation process of the human oocyte.…”
Section: Discussioncontrasting
confidence: 68%
“…This finding is in apparent contradiction to the suggestion that prolactin plays a role in inhibiting oocyte maturation (Baker and Hunter 1978). It is also at odds with a recent review; McNeilly (1984) concluded that evidence from a number of mammalian species indicated a role for prolactin at the ovarian level in influencing follicular growth and development.…”
Section: Discussioncontrasting
confidence: 54%
“…PRL may stimulate the formation of an oocyte maturation inhibitor in porcine granulosa cells |11|. Furthermore, treatment of cultured porcine follicles with an anti-PRL serum induces meiotic maturation [12]. These findings suggest that PRL may inhibit the nuclear maturation of oocytes.…”
Section: Discussionmentioning
confidence: 77%
“…PRL may stimulate the formation of an oocyte maturation inhibitor from porcine granulosa cells [11]. and treatment with an anti-PRL serum can induce meiotic maturation in cultured porcine follicles [12]. Therefore, the nuclear maturation of oocytes would appear to be impaired by PRL.…”
Section: Introductionmentioning
confidence: 99%